Unravelling Artemisia species genetic variation via DNA barcoding, ISSR and RAPD with the development of eco-specific SCAR markers - Yasmin A. Mahgoub; Hebaalla A. Mahmoud; Nadia A. El-Sebakhy; Ingy I. Abdallah (BMC Plant Biology)
Abstract Background Genus Artemisia is one of the largest and most globally spread genera, comprising more than 500 species known for their phytochemical diversity and therapeutic properties. This necessitates the accurate authentication and differentiation of its species. Traditional morphological, microscopical and metabolic profiling methods are often insufficient for reliable discrimination. The aim of this study is the authentication and assessment of the genetic diversity of wild Egyptian Artemisia species; A. herba-alba, A. monosperma, A. judaica and cultivated A. annua using a combined molecular approach of DNA barcoding, ISSR, RAPD, and the development of eco-specific SCAR markers. Results DNA barcoding targeting both nuclear (ITS2) and plastid (psbA-trnH) spacers revealed that ITS2 is recommended over psbA-trnH as the discriminatory barcode of choice since it accurately identified all species with > 99% identity and phylogenetic clustering with greater genetic distances. ISSR fingerprinting with five primers generated 41 polymorphic bands (100% polymorphism) and displayed genetic diversity among the species. However, the morphologically and chemically similar A. herba-alba and A. judaica remained partly undifferentiated. Therefore, RAPD profiling was implemented as a complementary technique for better and reliable discrimination. RAPD profiling with 27 primers generated 212 bands (99.5% polymorphic). RAPD primers OPA-10 and OPK-07 showed superior differentiation of the Artemisia species, while primers OPG-07, OPB-20, OPS-12 and OPD-15 failed to discriminate between the studied species. The reproducible RAPD banding profiles generated by OPG-02, OPG-04, OPA-09 and OPD-15 primers were targeted for the development of species-specific SCAR markers by isolating, cloning, and sequencing the distinct RAPD bands specific for each species. These putative SCAR markers were assessed and validated confirming the identity of the studied species. Conclusions An integrated molecular approach combining ITS2 barcoding, ISSR, RAPD, and RAPD-derived SCAR markers offered a reliable strategy for the authentication and discrimination of Artemisia species based on their genetic profiles. It is worth mentioning that this is the first report of eco-specific SCAR markers for the Egyptian Artemisia species. The developed SCAR markers allow rapid species identification for quality control of medicinal plants, complementing conventional methods and overcoming their limitations. This provides a reproducible, cost-effective strategy for large-scale authentication of medicinal plants.